(untitled) (MAUSAM, 2011)
. Utilizing surface vorticity fields computed with the ocean surface wind speed and direction data obtained from QuikSCAT, a study has been undertaken to investigate the increase in surface vorticity during the genesis phase of tropical cyclones over the north Indian Ocean. Six named tropical cyclones; Agni, Hibaru, Mala, Akash, Nargis and Phyan which formed over the region during 2004-2009 have been selected for this purpose. It has been found that there was a steep rise in scatterometer based surface vorticity before the formation of a cyclone in the cyclogenesis region. The peak surface vorticity in the genesis region was observed on the day of intensification of the vortex to the depression stage or a day earlier. However, the rising trend in the genesis region begins a few days before the formation of the system. Thus, the surface vorticity fields derived on the basis of scatterometer data can provide predictive indication of the genesis of tropical cyclones over the Bay of Bengal and Arabian Sea with a lead time of 2-3 days. Using this technique it is possible to increase the lead time of pre-cyclone watch period over the north Indian Ocean. No relationship was found between the peak surface vorticity anomaly during the genesis phase and the surface vorticity anomaly at the time of peak intensity of the system during its life cycle. In other words, the peak surface vorticity anomaly during genesis phase does not provide any indication of future maximum intensity of the cyclone.